2006 10th IEEE International Enterprise Distributed Object Computing Conference Workshops (EDOCW'06) 2006
DOI: 10.1109/edocw.2006.5
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Model of ICT-Supported Unified Process of International Outsourcing of Software Production

Abstract: This is an ongoing research in international outsourcing software production. This research examines how Software production through the ICTsupported unified process of international outsourcing could be executed and managed effectively. To address this research question, the results of an in-depth literature review in the areas of outsourcing, international outsourcing, information technology, and international software production is presented. This study proposes the information communication technologies' (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…& Two of the studies selected (Yalaho 2006;Shaw and Clements 2006) would not have been included in the original tertiary, because they did not have a clear data extraction and aggregation process, although they did have a defined search process. & Two of the studies that investigated empirical software engineering (Segal et al 2005;Höfer and Tichy 2007) considered only one source (i.e.…”
Section: P11: a Broad Automated Search Will Identify More Relevant Pmentioning
confidence: 99%
“…& Two of the studies selected (Yalaho 2006;Shaw and Clements 2006) would not have been included in the original tertiary, because they did not have a clear data extraction and aggregation process, although they did have a defined search process. & Two of the studies that investigated empirical software engineering (Segal et al 2005;Höfer and Tichy 2007) considered only one source (i.e.…”
Section: P11: a Broad Automated Search Will Identify More Relevant Pmentioning
confidence: 99%
“…Effective outsourcing requires that clients and vendors have adequate level of shared knowledge concerning the components and services being provided (Yalaho, Nahar, Käkölä., & Wu, 2002). Sung and Young (2003), who investigated the success and failures of outsourcing projects, suggested that a strong formation of relational exchange attributes between vendor and client is essential to successful project implementation.…”
Section: Challenges To Outsourcing Successmentioning
confidence: 99%
“…This study reveals that SME mainly outsource software development striving for increased flexibility and better skill access rather than mere cost savings. Mitigating these risks requires a structured approach in the shape of a risk management process [25], for example, or simply guiding principles for a sourcing decision that enable systemic thinking [6]. This is particularly challenging for smaller firms who are characterized by less structural formalism [4].…”
Section: Introductionmentioning
confidence: 99%